Analisis Yuridis Alih Fungsi Tanah Kas Desa Untuk Pembangunan Kolam Renang di Desa Udanwuh - Suwoto, Suwoto; Santoso, Aris Priyo Agus; Hastuti, Indra; Elisanti, Evi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The aim of this research is to determine the regulation of the transfer of land to the village treasury and the obstacles of the Udanwuh Village government to building a swimming pool. The research location is at the Udanuwuh Village Hall Office, Kaliwungu District, Semarang Regency. The type of research used is an empirical juridical approach. The type of data, namely primary data, was obtained through interviews and discussions with several parties in order to provide information related to the transfer of land to the village treasury. Secondary data was obtained from library literature. Data collection techniques through literature study, interviews. Qualitative descriptive data analysis techniques. The results of the research show that the arrangement for the conversion of Village treasury land for the construction of a swimming pool in Udanwuh Village is in the form of government land in Udanwuh Village on title C Village Number 4, Plot 29 Class SII located in Ngrancah Hamlet RT.03 RW.02 village treasury land with a total area of + /- 833m2 and for the construction of swimming pools of +/-753 m2 and +/-130 m PDAM is used. Obstacles related to licensing for the conversion of village treasury land for the construction of swimming pools are based on Semarang Regency Regional Regulation No. 14 of 2003. However, with the issuance of Regional Regulation No. 21 of 2021 concerning the revocation of Semarang Regency Regional Regulation No. 14 of 2003, this has resulted in permits not being completed or delayed. The conclusion of the research is that the conversion of land functions in order to comply with applicable regulations, has a positive impact on the progress of the village, optimal management of land conversion, maximum utilization of the function of the Village treasury land into a swimming pool to improve the village economy and village community, resolving solutions to problems in make regulations regarding the transfer of cash land functions in the construction of swimming pools.